EFFORTS OF NOTARIES/PPAT IN PROVIDING LEGAL PROTECTION FOR PARTIES THROUGH AGREEMENTS MADE TO PREVENT DISPUTES IN DEBT TRANSACTIONS SECURED BY LAND SALES AGREEMENTS AS COLLATERAL - Aprilia, Innike Ilena; Hamidah , Siti; Susilo, Hariyanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
Basically, agreements entered into by the parties must be in the form of a legally certain agreement, executed in writing to serve as strong evidence in the event of disputes. Subsequently, what is the role of a Notary/PPAT in providing legal protection in land purchase agreements to prevent debt and credit disputes? This research will analyze how the steps taken by a Notary/PPAT are based on existing legal provisions to ensure the validity of the agreement and protect all parties involved. Through an analysis of legal regulations related to the role of a Notary/PPAT in property transactions and identifying specific steps taken by a Notary/PPAT based on applicable law, this study aims to ensure the validity of the agreement and provide protection to all parties involved.